Suriname : 2019 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Suriname discusses that Suriname continues to grow steadily with low inflation. However, there has been little progress in implementing urgently needed fiscal reforms, and the fiscal position is likely to continue to weaken in the coming year. The consultation focused on policies to bolster the economy in the medium term. These include fiscal measures to enhance revenues and efficiency and lower expenditures, policies to improve the monetary and financial sector supervision frameworks, and structural policies to boost potential growth. Advances have been made in developing the central bank's monetary tools and facilities; however, more is needed to strengthen the credibility of the monetary framework. The banking sector faces important downside risks and there are gaps in the central bank's supervisory and resolution framework. It is advised to put the public debt on a sustainable path. A significant reduction in the fiscal deficit could be achieved by implementing a value-added tax, curtailing electricity subsidies except to the poor, and improving public financial management.